2020
DOI: 10.21031/epod.702191
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Literacy of Students in Turkey by Years and School Types: Performance of Students in PISA Applications

Abstract: The assessment of students' academic achievement via international monitoring studies provides important insights to participating countries. Besides the cognitive performance of students, educational equity is one of the emphasized topics within the scope of Programme for International Student Assessment (PISA) study. Results regarding educational equity are quite important in Turkey because academic achievement differences among school types are relatively high in Turkey. Although a wide range of studies is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Studies show that, when students are placed in schools based on their academic performance, achievement gaps between school types increase (Karaağaç Cingöz & Gür, 2020;Suna et al, 2020a, Suna et al, 2020c. Clustering comparatively low-performing students in a particular school type such as VTAHs leads to higher levels of absenteeism and even school dropout (Bölükbaş & Gür, 2020;Suna et al, 2020a;Suna et al, 2020b). Some VET graduates also attribute their out-of-field employment to low quality education at VET schools, even though the problem only becomes visible in the labor market.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that, when students are placed in schools based on their academic performance, achievement gaps between school types increase (Karaağaç Cingöz & Gür, 2020;Suna et al, 2020a, Suna et al, 2020c. Clustering comparatively low-performing students in a particular school type such as VTAHs leads to higher levels of absenteeism and even school dropout (Bölükbaş & Gür, 2020;Suna et al, 2020a;Suna et al, 2020b). Some VET graduates also attribute their out-of-field employment to low quality education at VET schools, even though the problem only becomes visible in the labor market.…”
Section: Discussionmentioning
confidence: 99%
“…Son olarak, Türkiye'de eğitim sistemi ile ilgili temel problemlerden bir tanesini okullar arası başarı farkları oluşturmaktadır (Bölükbaş ve Gür, 2020;Cingöz ve Gür, 2020;Güllüpınar ve İnce, 2014;Oral ve Mcgivney, 2014;Suna, Tanberkan ve Özer, 2020;Suna vd, 2020a;2020b). MEB, bu problemin eğitim sistemi üzerindeki etkisini azaltmak için yıllardan beri çalışmakta ve her geçen gün soruna çok-boyutlu yaklaşan yeni projeler geliştirmektedir (Gençoğlu, 2019;Özer, 2021;Özer, Gençoğlu ve Suna, 2020).…”
Section: Tartışma Ve Politika öNerileriunclassified
“…PISA 2012 and 2015 results also confirmed the dramatic differences in test performance across high school types in Turkey (MEB, 2016;World Bank, 2013). Suna, Tanberkan and Ozer (2020) analyzed the distribution of students in a Turkish sample of basic and advance levels of proficiency by school types between PISA 2003 and PISA 2018. It was found that there are significant and remarkable differences in ratios of students who have a basic and advance level of proficiency between school types in all literacy areas.…”
Section: School Types and Transition Systems In Turkeymentioning
confidence: 99%